Adenylosuccinic Acid: An Orphan Drug with Untapped Potential - Emma Rybalka; Stephanie Kourakis; Charles A. Bonsett; Behzad Moghadaszadeh; Alan H. Beggs; Cara A. Timpani (MDPI AG, 2023)
Adenylosuccinic acid (ASA) is an orphan drug that was once investigated for clinical application in Duchenne muscular dystrophy (DMD). Endogenous ASA participates in purine recycling and energy homeostasis but might also be crucial for averting inflammation and other forms of cellular stress during intense energy demand and maintaining tissue biomass and glucose disposal. This article documents the known biological functions of ASA and explores its potential application for the treatment of neuromuscular and other chronic diseases.